Symmetric intertriginous flexural rash related to topical polyvalent - Briceño, Monica (2022)
The case of a 12-year-old patient is presented, who 5 hours after the application of a topical polyvalent presents an increase in volume at the level of the penis and scrotum, presenting with erythema in flexural areas of the groin, armpit, back of the feet and marked erythema symmetrical in buttocks with pasty skin, referring to intense itching on a 9/10 scale in the lesions. In laboratory tests hemogram without leukocytosis and eosinophils 18%. Normal testicular echo-Doppler. Topical corticosteroid and prednisone were indicated, with remission of pruritus and erythema, being discharged 6 days later. With little desquamation in the buttocks, due to meeting the criteria for drug exposure, V-shaped erythema, flexural compromise, absence of systemic repercussion and symmetric involvement is reported as a drug-related symmetric intertriginous flexural rash (SDRIFE).